Analysis of the Effectiveness of the Roles of Writers and Public Figures as Reading Ambassadors: A Comparative Study in Encouraging the Improvement of Community Literacy - Hardianty, Sri; Ismawan, Dana (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This study aims to analyze the effectiveness of the roles of writers and public figures as reading ambassadors in promoting literacy culture and increasing reading interest in the community. The formulation of this research focuses on the comparison of strategies used by writers and public figures in spreading literacy messages, as well as the impact of both roles on society. The method used in this research is a comparative study with a qualitative approach, which involves collecting and analyzing data from various written sources, including books, articles and related reports. The results show that authors, through their profound and inspiring literary works, are able to create a captivating reading experience and build a strong emotional connection with readers. On the other hand, public figures utilize their popularity and extensive networks on social media to spread literacy messages in a more direct and interactive way, reaching a larger audience in a short period of time. Despite the differences in approaches and strategies used, collaboration between writers and public figures has been shown to strengthen literacy promotion efforts. This study concludes that the synergy between these two roles can create a significant impact in improving the reading culture in society. By utilizing their respective strengths, writers and public figures can jointly encourage higher reading interest and provide sustainable benefits for the social and intellectual development of the community.